PENGARUH KOMBINASI TWEEN 80 DAN MALTODEKSTRIN TERHADAP KARAKTERISTIK FLAVOR ENHANCER IKAN BULAN-BULAN (Megalops cyprinoides) - Cahyani, Reni Tri; Nadia, laode Muhamad Hazairin (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2022)
One method that can be applied in the production of flavor enhancers is the foam-mat drying method using Tween 80 and maltodextrin. This research aimed to examine the effect of the Tween 80 and maltodextrin combination on the characteristics of flavor enhancers from Megalops cyprinoides. This research used a factorial completely randomized design with two factors. Factor one was Tween 80 concentration of 2%, 4%, and 6%, and factor two was maltodextrin concentration of 10%, 20%, and 30%. The test parameters included yield, pH, and Maillard reaction products. The results showed that Tween 80 and maltodextrin concentration significantly affected yield, pH, and Maillard reaction products of flavor enhancers from Megalops cyprinoides (P0.05). The greater the concentration of Tween 80 and maltodextrin, the greater the yield value, while the Maillard reaction product value decreased. Increasing the concentration of maltodextrin caused the pH value to decrease. Conversely, increasing the concentration of Tween 80 caused the pH value to increase. Based on the research result, the best treatment was Tween 80 concentration of 6% and maltodextrin concentration of 10%, with the yield of 43.33%; pH of 3.78; and Maillard reaction product 0.608 AU.